PERBEDAAN PENGARUH MODEL PEMBELAJARAN JIGSAW DAN MAKE A MATCH TERHADAP PRESTASI BELAJAR SEJARAH DITINJAU DARI KREATIVITAS BELAJAR SISWA KELAS XI SMA NEGERI DI KABUPATEN SAMBAS TAHUN 2015/2016 - Dediansyah, Agus; Akhyar, Muhammad; Musadad, Akhmad Arif (Sebelas Maret University (UNS), 2015)
Background: This study aims to find out the difference effect between Jigsaw and â€œMake a Matchâ€ learning models toward learning achievement of History; The difference effect between high learning creativity and low learning creativity to the learning achievement of History; The interactioneffect between the model of learning and learningcreativity in learning achievement of History.Methods: This study uses a quantitative approach to experiment with factorial design 2 x 2. The population in this study were all students of Class XI SMA Sambas District, West Kalimantan Province in the academic year 2015/2016. The sampling technique used is the technique of multi-stage cluster random sampling. In this study, the sample were students of class XI IPS SMAN 1 and SMAN 2 Sambas Tebas. Data collection techniques used is tests and questionnaires. Data analysis technique used is Analysis of Variance (ANOVA) Two Line. Before analysis, validity test conducted by Product Moment correlation, reliability using Cronbach's alpha and KR 20 test for normality and homogeneity test.Results: There are differences in learning achievement between students who learn history by using Jigsaw learning models and Make a Matchmodels. Make a Match learning model generating learning achievement is better than the Jigsaw learning model, and there are differences in academic achievement between students who have high and low creativityof learning history. Students with high creativity better learning achievement compared to the low learning creativity, and there is no interaction effect between teaching model with the creativity of the students' learning achievementof history.Conclusion: There is a difference effectsbetween the learning model of Jigsaw and Make a Match with Learning creativity, and there is no interaction between the model of learning by learning creativity toward student learning achievement history.